MACROSCOPIC TURBULENCE MODEL ADJUSTMENT FOR A POROUS MEDIUM MODELED AS AN INFINITE ARRAY OF TRANSVERSALLY-DISPLACED ELLIPTIC RODS - Pedras, M. H. J.; de Lemos, M. J. S. (Revista de Engenharia Térmica, 2003)
Through the volumetric averaging of the microscopic transport equations for the turbulent kinetic energy, k, and its dissipation rate, , a macroscopic model was proposed for flow in porous media (Pedras and de Lemos, IJHMT 44 (6) 2001). As an outcome of the volume averaging process, additional terms appeared in the equations for k and . These terms were here adjusted assuming the porous structure to be modeled as an infinity array of transversal elliptic rods. Such an adjustment was obtained by numerically solving the microscopic flow governing equations, using a low and high Reynolds formulation, in the periodic cell composing the infinite medium. Different porosity and aspect ratios were investigated. The adjusted model was compared against others types of rods found in the literature, showing similar results.